miR-16-5p Suppresses Progression and Invasion of Osteosarcoma via Targeting at Smad3 - Gu, Zhijian; Li, Zhikun; Xu, Ruijun; Zhu, Xiaodong; Hu, Ruixi; Xue, Yonghua; Xu, Wei (Frontiers in Pharmacology, 2020)
Background: MicroRNAs are known to regulate carcinogenesis of osteosarcoma. Although, miR-16-5p is known to exert inhibitory effects on several forms of cancers, its effects on the growth and invasion of osteosarcoma have not been studied. Methods: We collected human osteosarcoma specimens and adjacent tissues to detect the expression of miR-16-5p by real-time polymerase chain reaction, immunoblotting, and immunohistochemistry. The proliferation, migration, and invasion of MG63 and HOS cells following miR-16-5p overexpression and inhibition were detected with cell counting kit-8, wound healing assay, and transwell assay, respectively. An expression vector carrying a mutated 3′-untranslated region of mothers against decapentaplegic homolog 3 (Smad3) was constructed. Results: The results showed that miR-16-5p expression was downregulated in osteosarcoma tissues and cells as compared with adjacent counterparts, while Smad3 was overexpressed in osteosarcoma cells. The overexpression of miR-16-5p resulted in the inhibition of the proliferation, migration, and invasion of osteosarcoma cells and enhanced the therapeutic effect of cisplatin. These effects were attenuated with miR-16-5p expression inhibition. In cells transfected with miR-16-5p mimic, Smad3 expression decreased, while this effect was absent in the cells carrying mutated Smad3. Conclusions: Therefore, miR-16-5p inhibits the growth and invasion of osteosarcoma by targeting Smad3.